1951
DOI: 10.1002/macp.1951.020070209
|View full text |Cite
|
Sign up to set email alerts
|

Über ein polymeres 2,3‐dimethylbutadienperoxyd

Abstract: Bei der Autoxydation von 2,3-Dimethylbutadien entsteht ein polymeres Peroxyd, das Lich zumindest vorwiegend dur& alternierende 1,2-Mis&polymerisation des Diens mit molekularem Sauerstoff bildet. Durch theimischc Zersetzung des polymeren Peroxyds in Suspension oder P erdunnnng wurden als Bruchstucke Formaldehyd nnd Isopropenylrnethylketon isoliert und identifiriert. Ein monomeres Dimethylbutadienperoxyd wurde nicht heobachtet. S U M M A R Y :The autoxydation of 2,3-dimethylbutadien yields a polymer peroxyd. Dim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
4
0

Year Published

1955
1955
1975
1975

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…Using this value, the enthalpy of formation of solid OC(OH)2 is calculated t o be AHf = -155 +-10 kcal/ mole. This value is in good agreement with the enthalpy of formation calculated by the increments method [7] and estimated from the thermochemical data for carbonates [5,8] and trithiocarbonates [8,9].…”
Section: On the Preparation Of "Free Carbonic Acid"supporting
confidence: 86%
See 2 more Smart Citations
“…Using this value, the enthalpy of formation of solid OC(OH)2 is calculated t o be AHf = -155 +-10 kcal/ mole. This value is in good agreement with the enthalpy of formation calculated by the increments method [7] and estimated from the thermochemical data for carbonates [5,8] and trithiocarbonates [8,9].…”
Section: On the Preparation Of "Free Carbonic Acid"supporting
confidence: 86%
“…Both isomers have characteristic infrared absorptions [4]: the epoxide bands of (2) are at 1237, 899, and 802 cm-1; those of (3) are at 1241, 897, and 810 cm-1 [5]. Chemical proof of the structures of (2) and (3) is supplied by reduction with LiAIH4 to give (5), and by hydrolysis with acid to give the stereoisomeric tetrahydrofuran-2,3-diols; here (2) yields the cis-form (6), and (3) leads to the trans-compound (7) [61.…”
Section: On the Preparation Of "Free Carbonic Acid"mentioning
confidence: 99%
See 1 more Smart Citation
“…The oxidation of reactive olefins is known to be important in their deterioration (76, 79). Previous studies indicate that an acyclic conjugated diene may be representative of the cracked-gasoline component that undergoes autoxidative deterioration (6,8,9). Others have considered the reaction (7 7) of diene, mercaptan, and oxygen to be a predominant cause of gum formation in heavier fuels (24).…”
mentioning
confidence: 99%
“…The formation of acetone and p-methylcrotonaldehyde can be explained by cleavage of 1,2-peroxo-linked structures (B) [7]. Since the amount of acetone formed is 5 %, it can be concluded that the ratio of C~H …”
mentioning
confidence: 99%